Phosphorylation of eIF4E by Mnk-1 enhances HSV-1 translation and replication in quiescent cells - Walsh, Derek (Cold Spring Harbor Laboratory Press, 2004)
Although the activity of the translation initiation factor eIF4F is regulated in part by translational repressors (4E-BPs) that prevent incorporation of eIF4E, the cap-binding protein, into the initiation complex, the contribution of eIF4E phosphorylation to translational control remains controversial. Here, we demonstrate that the herpes simplex virus-1 (HSV-1) ICP0 gene product, a multifunctional transactivator of viral gene expression with ubiquitin E3 ligase activity that is important for vegetative replication and reactivation of latent infections, is required to stimulate phosphorylation of eIF4E as well as 4E-BP1, and promote assembly of eIF4F complexes in infected cells. Furthermore, 4E-BP1 is degraded by the proteasome in an ICP0-dependent manner, establishing that the proteasome can control 4E-BP1 steady-state levels. Preventing eIF4E phosphorylation by inhibiting the eIF4E kinase mnk-1 dramatically reduced viral replication and the translation of viral polypeptides in quiescent cells, providing the first evidence that phosphorylation of eIF4E by mnk-1 is critical for viral protein synthesis and replication. Thus, in marked contrast to many viruses that inactivate eIF4F, HSV-1 stimulates eIF4F complex assembly in quiescent, differentiated cells; moreover, this is important for viral replication, and may be crucial for HSV-1 to initiate its productive growth cycle in resting cells, such as latently infected neurons.